Bridging the knowledge gap on vaping - Look, Keyun; Ser, Hooi Leng *; Amar, Daud Iskandar Abdullah *; Elil, Renganathan *; Long, Chiau Ming * (Star Media Group Berhad, 2023)
Despite the established health risks associated with vaping, there remains a significant gap in public awareness, especially among youths. The widespread misconception that vaping is a safer alternative to traditional cigarettes has fuelled their rising popularity.